Factors Associated with Exclusive Breastfeeding on Infants Aged 6-12 Months in Harapan Baru Public Health Center, Samarinda - Ni Wayan Wiwin Asthiningsih (Global Health Science Group, 2021)
Exclusive breastfeeding has a great contribution to the growth and development and endurance of children. According to the World Health Organization (WHO) in the Indonesian Ministry of Health (2017), exclusive breastfeeding is breast milk that is given to babies from birth for 6 months, without adding and/or replacing with other foods or drinks. There are several factors that can affect the exclusive breastfeeding. This study aims to determine what factors associated exclusive breastfeeding in the working area of Harapan Baru Public Health Center, Samarinda. The research design used in this research is descriptive correlational. The sample in this study amounted to 107 infants aged 6-12 months. The sampling technique used cluster sampling. Data collection was carried out using a questionnaire. The data analysis technique used Chi Square. The results showed that the factors that associated exclusive breastfeeding in the work area of the Harapan Baru Public Health Center, Samarinda were the parity (0.038 < 0.05), employment status (0.040 < 0.05), socioeconomic status (0.017 < 0.05), family support (0.006 < 0.05), early initiation of breastfeeding (0.009 < 0.05). The factors most related to exclusive breastfeeding are family support and early initiation of breastfeeding.